Maatalouden verotus Saksassa - Miettinen, Mia (Maatalouden taloudellinen tutkimuslaitos, 1998)
Maatalouspolitiikan suhteen EU:n jäsenmaiden kansallinen liikkumavara on vähäinen. Verotus ja sosiaalipolitiikka kuuluvat kuitenkin melko pitkälle kansallisen päätäntävallan piiriin. Maa- ja metsätalousministeriön rahoittamassa tutkimushankkeessa on selvitetty Saksan maatalousverojärjestelmää saksalaisviljelijöiden mahdollisten kilpailuetujen ja -haittoja arvioimiseksi suomalaisiin viljelijöihin verrattuna. Tutkimuksesta käy ilmi, että saksalaisviljelijöiden maksettavaksi tulevan tuloveron määrä on noin 50 % alhaisempi kuin Suomessa. Saksassa maataloudenharjoittajien pakolliset sosiaalivakuutusmaksut ovat kuitenkin huomattavasti korkeammat kuin Suomessa. Vertailu osoittaa saksalaisten ja suomalaisten tilojen maksurasitteen olevan lähes yhtä suuren. Saksassa perintö- ja lahjaverosäännöstöstä on muodostettu selkeä kansallinen tukimuoto maataloudelle. Useat päällekkäiset vapaaosat, omaisuuden arvostamissäännökset ja siviilioikeudellisen lainsäädännön säännökset saavat aikaan sen, että vähennysten jälkeen maatiloille ei pääsääntöisesti jää maksettavaksi perintö- tai lahjaveroa, eikä tilanpidon jatkaja juuri koskaan maksa sukupolvenvaihdosluovutuksesta erillistä vastiketta. Saksassa tuloverotuksen edullisuus johtuu useista päällekkäisistä vähennyksistä. Ensin kunkin tulolajin sisällä vähennetään tulonhankkimismenot, jonka lisäksi kaikkien tulojen yhteissummasta tehdään vähennyksiä, joita ei voida kohdistaa yksittäisiin tulolajeihin. Saksassa suuret tilat ovat velvollisia pitämään kahdenkertaista kirjanpitoa. Hieman tätä pienemmät tilat ilmoittavat tulot kassaperusteisen meno-tulolaskelman mukaisesti. Kolmas menetelmä on kaavamainen pinta-alaperusteinen menetelmä, jossa todellisista tuloista tulee verotettavaksi 45-75 %. Tässä menetelmässä tuloverotus on edullisimmillaan, mutta sitä voivat käyttää vain pienet, tulokseltaan heikohkot ja sivutoimiset tilat. Mikäli maataloudenharjoittaja ei täytä ilmoitusvelvollisuuttaan, tulot arvioidaan. Arviointimenetelmä on ollut perinteisesti monille pientiloille edullinen, joten siihen ajaudutaan usein harkitusti. Saksan vuonna 1996 uudistettu perintö- ja lahjaverosäännöstö ulotti yritysten sukupolvenvaihdoksia koskevat veronhuojennukset myös maatalouteen. Perittäessä tai lahjoitettaessa maatalous- ja yritysomaisuutta omaisuuden arvosta voidaan vähentää 500 000 DM:n vapaaosa ja jäljelle jäävästä summasta vielä 40 %. Huojennus kohdistuu maatilan peltoihin, metsään ja maataloustyöntekijöiden asuntoihin. Käteisvarat ja maanviljelijän oma asunto lisätään huojennettuun omaisuuteen. Huojennuksen ja muiden vähennysten jälkeen lahjansaaja tai perillinen voi vähentää oman henkilökohtaisen vapaaosansa, joka on rintaperillisillä 400 000 DM. Saksan perintö- ja lahjaverotuksen edullisuus johtuu myös omaisuuden arvostusmenettelystä, jossa maatilan irtaimen omaisuuden, talousrakennusten, eläinten ja maitokiintiön arvo sisällytetään maapohjan arvoon. Käytännössä niiden osuus lopullisesta perintö- ja lahjaverotusarvosta on olematon. Uudistetun arvostusmenettelyn pohjalta määritettävät maapohjan arvot ovat lähellä tämän päivän reaalisia tuottoarvoja. Uudistuksessa arvot nousivat huomattavasti, mutta vastaavasti henkilökohtaisia vapaaosia nostettiin entisestä. Maatilojen sukupolvenvaihdosluovutusten edullisuuden takana vaikuttavat myös siviilioikeudelliset ja alueelliset sukupolvenvaihdosluovutuslait, joiden tarkoituksena on taata, että tila ei siirry suvun ulkopuolelle. Jatkajan kannalta siviilioikeudellisten sukupolvenvaihdoslakien suurimman hyödyn muodostavat lain sanelemat pienet väistyvien perillisten korvaukset ja se, että vanhemmille tuleva korvaus muodostuu yleensä vain syytingistä.

The study is composed of two parts. He first part studies farmers income taxation in Germany. In Germany farmers may report their annual income for taxation according to three different taxation procedures. Large farms are obliged to double-entry bookkeeping and to report their incomes according to this. Smaller farms report their incomes according to cash basis expenditure and income calculation, and the information value of this is somewhat weaker than that of double-entry bookkeeping. The third procedure is a fully schematic method based on the area, and through this only about 45-75% of the real income can be taxed. This method can be used only by small farms with weak results or part-time farms. The income taxation is the lowest when using the third method, which is based on averages. If a farmer fails to fulfill the reporting obligation, an estimation procedure of incomes is applied. The estimation procedure differs from the Finnish tax assessment by estimation in that it has traditionally been beneficial for many small farms, and thus it has been used deliberately. Farmers cannot choose the procedure to be used, but they are directed to the appropriate procedure on the basis of the size, result and economic value of the farm. If the farm size or the result changes, the farmer may change the procedure, but the change is binding for a certain period of time. When the amount of income taxes to be paid by German farms are examined, it can be noted that these are about 50% lower than in Finland. Income taxation is the lowest when the taxpayer is married. The German legislation on income taxes is constructed so that the spouses may use tax tables of their own, and thus enjoy considerable tax concessions. The low income taxation is also partly caused by several overlapping deductions, which are first made within each type of income and, finally, deductions are made on the total of all types of income that could not be made in the case of the individual types of income. However, when the obligatory social security payments comparable to taxes in the countries in question were taken into account in addition to the amount of income taxes, the research result changed in a significant way. The social security expenses of German farmers are considerably higher than in Finland. Consequently, the burden caused by such payments on the Finnish and German farms is almost equal - on the German bookkeeping farms it is even a little higher than in Finland. This can be seen in the farm models presented in the latter part of the study. The second part of the study considers inheritance and gift duties of farms in Germany. The stipulations on inheritance and gift duties in Germany revised in 1996 extended the tax concessions concerning the change of generation in companies to agriculture as well. When agricultural or company property is inherited or given away, concession according to section 13a of the act is directed to the property. Based on this concession, a free share of DM 500,000 can be deducted from the value of the property, and a further deduction of 40% can be made on the remaining amount. The concession concerns the arable land and forest of farms as well as residences of farm workers. Cash funds and the residence of the farmer are added to the property on which the concessions have been made. In addition to this concession, the recipient of the gift or heir may deduct a personal free share after all other deductions. In the case of direct heirs the personal free share is DM 400,000. Due to the several overlapping free shares, in most cases there remain no inheritance or gift duties to be paid by farms. The low inheritance and gift duties in Germany are also partly based on the valuation of property in which the movable property, production buildings, animals or milk quotas are not valued separately. In practice the share of these of the final inheritance and gift duty value is DM 0. After the reform the old unit values defined in 1964 are no longer used as the basis for inheritance and gift duties. These were replaced by the first uniform valuation procedure applied in the whole country, and the values determined on the basis of this are close to the current realistic productive values of the ground. Thus the values rose considerably, but this was compensated by raising the personal free shares. One reason for the low payments in connection with changes of generation is also the regional act concerning the transfer of farms to descendants (Höfeordnung) based on the civil law, which makes sure that the farm is not transferred outside the family. The most significant benefits of acts concerning the change of generation that are based on the civil law consist of the small compensations to the heirs yielding the property and life-annuity to the parents. As a result of these factors the heir remaining on the farm hardly ever pays any separate compensations in connection with the transfer of the farm. Consequently, the low inheritance and gift duties in Germany are based on several overlapping free shares, valuation of the property, as well as stipulations based on the civil law that guarantee very low or no payments in connection with the transfer of a farm.
Keywords: Ma; Saksa; maatalous; tulovero; lahjavero; perintövero; agriculture; Germany; gift duties; income taxation; inheritance duties